1984
DOI: 10.1152/jappl.1984.57.5.1577
|View full text |Cite
|
Sign up to set email alerts
|

Insulin acts on the fibroblast to inhibit glucocorticoid stimulation of lung maturation

Abstract: The effects of insulin and cortisol on saturated phosphatidylcholine synthesis are examined in fetal type II cell cultures and in mixed cell cultures containing type II cells and fibroblasts. In 19-day fetal rat lung type II cell cultures, 100 nM cortisol and 2 nM insulin have no significant effect. Fibroblast-pneumonocyte factor results in enhanced saturated phosphatidylcholine synthesis by fetal type II cells. The significant stimulatory effect of cortisol in mixed-cell cultures is abolished in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Without appropriate monitoring and adjustment of insulin dosage, this, in turn, may create an increased risk of severe dysregulation with ketoacidosis. With maternal hyperglycaemia, fetal lung development may also be compromised [ 59 ], potentially offsetting any benefits of ACS therapy to the infant. However, direct evidence for this is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Without appropriate monitoring and adjustment of insulin dosage, this, in turn, may create an increased risk of severe dysregulation with ketoacidosis. With maternal hyperglycaemia, fetal lung development may also be compromised [ 59 ], potentially offsetting any benefits of ACS therapy to the infant. However, direct evidence for this is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Corticoids accelerate fetal lung maturation and cause alveolar wall thinning, alteration of alveolar wall composition, and an increase in the volume of air spaces (Kikkawa et al, 1971;Massaro and Massaro, 1986) as well as biochemical lung maturation as shown by glycogen deposition and surfactant synthesis (Rooney et al, 1986;Juanes et al, 1986). On the other hand, insulin is known to inhibit fetal lung maturation because insulin antagonizes the action of corticoid (Carlson et al, 1984;Smith et al, 1975). Therefore, delayed maturation of the lung in the fetuses from diabetic dams may be due to fetal hyperglycemia, hyperinsulinemia, or both.…”
Section: Discussionmentioning
confidence: 99%
“…45 Antenatal glucocorticoid therapy causes a transient increase in maternal glucose concentrations, [46][47][48] often more pronounced in women with diabetes, 46,49 and some 47 but not all 50 randomized trials have shown an increase in the incidence of glucose intolerance in women following glucocorticoid administration. While hyperglycemia and hyperinsulinism can impair glucocorticoid action, [51][52][53] outcomes appear similar for preterm infants of mothers with and without diabetes when there is adequate maternal glycemic control and a high rate of antenatal glucocorticoid exposure. 54,55 Consequently, antenatal glucocorticoid therapy remains indicated in women with diabetes, 11 although increased insulin therapy may be required.…”
Section: Obstetric Subgroupsmentioning
confidence: 99%